Potential of mass-production and field efficacy of isolates of the entomopathogenic fungi Beauveria bassiana and Paecilomyces fumosoroseus against Plutella xylostella - Ibrahim, Y.B.; Low, W. (Taylor & Francis Group, 1993)
Studies were conducted to examine the possibility of using entomogenous fungi to control the diamondback moth (DBM), Plutella xylostella in Serdang, Selangor, Malaysia. Results from mass‐culturing indicated that rice was most suitable for growth and sporulation amongst the loose‐solid media tested and coconut water for the liquid media. Three applications of spore suspensions of Beauveria bassiana and Paecilomyces fumosoroseus each applied at a dilution of 1 χ 108spores/ml at a rate of 3.75 χ 1013spores/ha were required to cause significant reduction (?<·05) in the larval population of DBM. Sprays of permethrin (·025%) on plants already treated with B. bassiana showed no added improvement to the protection of the cabbage leaves. Alternating sprays of cypermethrin (0.01%) and phenthoate (0.1%) did not significantly increase the yield of marketable cabbage heads when compared with plots treated with the entomopathogens. The virulence of both fungal species was maintained throughout the duration of the experiment.